Information, externalities and socioeconomics of Malaria in Honduras: A preliminary analysis - Maria Victoria Avilés; José Cuesta (Inter-American Development Bank, Research Department, 2009)
This paper explores how different levels of knowledge correlate with desirable preventive and curative practices against malaria in Honduras. The paper additionally analyzes 'information externalities' associated with non-specific malaria health services, communicational campaigns and organized community networks. Using the 2004 ENSEMAH survey, the analysis tests for statistical differences in the means of behavioral variables and an index of household malaria knowledge, finding that the adoption of desirable prevention and treatment behaviors correlates with proficient levels of knowledge. Differences in behavior across groups with distinctive levels of proficiency were found statistically significant. Also, while information externalities exist, they nonetheless do not deliver adequate levels of knowledge proficiency to induce desirable anti-malaria behavior.
Keywords: D19; H49; H75; I19; 330; Malaria; Information; Externalities; Honduras